Case report: endovascular stenting in peripheral arterial disease of lower extremity - Oktaviono, Yudi Her (Folia Medica Indonesiana, 2017)
Peripheral arterial disease (PAD) is usually caused by multilevel atherosclerotic disease, typically in patients with a history of cigarette smoking, diabetes mellitus, or both. Intermittent claudication (IC), an early manifestation of PAD, commonly leads to reduced quality of life for patients who are limited in their ambulation. Percutaneous intervention for peripheral artery disease has evolved from balloon angioplasty for simple focal lesions to multimodality techniques that enable treatment of severe arterial insufficiency. Especially for high-grade stenoses or short arterial occlusions, percutaneous transluminal angioplasty (PTA) should be the method of first choice followed by the best surgical procedure later on. To achieve good long-term efficacy, a close follow-up including objective tests of both the arterial lesion and hemodynamic status, surveillance of secondary preventive measures and risk factor control is mandatory.